2010
DOI: 10.2478/s11535-010-0062-9
|View full text |Cite
|
Sign up to set email alerts
|

Early stress affects neurogenesis in the rat rostral migratory stream

Abstract: Early stress affects neurogenesis in the rat rostral migratory stream Abstract: Stressful experience during the early postnatal period may influence processes associated with neurogenesis (i.e. proliferation, cell death, appearance of astrocytes or cell differentiation) in the neonatal rat rostral migratory stream (RMS). To induce stress, pups were subjected to maternal deprivation daily for three hours, starting from the first postnatal day till the seventh postnatal day. Immunohistochemical methods were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(41 reference statements)
0
3
0
Order By: Relevance
“… 28 Our results of quantitative analysis showed, that the response of Ki-67-positive cells to stress was not uniform in the vertical arm, elbow and horizontal arm of the RMS. Unlike the overall decrease of BrdU labeled cells in all three parts of the RMS following maternal deprivation, 35 the decrease of the number of Ki-67-positive cells was restricted only to the RMS caudal part, i.e., to the vertical arm. Surprisingly, in the elbow and in the horizontal arm of the RMS we have observed increased amount of proliferating cells.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“… 28 Our results of quantitative analysis showed, that the response of Ki-67-positive cells to stress was not uniform in the vertical arm, elbow and horizontal arm of the RMS. Unlike the overall decrease of BrdU labeled cells in all three parts of the RMS following maternal deprivation, 35 the decrease of the number of Ki-67-positive cells was restricted only to the RMS caudal part, i.e., to the vertical arm. Surprisingly, in the elbow and in the horizontal arm of the RMS we have observed increased amount of proliferating cells.…”
Section: Discussionmentioning
confidence: 58%
“…Maternal deprivation induced striking changes also in proliferation activity of Ki-67-positive neuronal precursors within the migratory pathway. Using a similar experimental paradigm, previously we have shown that maternal deprivation 35 caused significant changes in the number of proliferating cells labeled with the S-phase marker BrdU within the rat RMS. BrdU immunohistochemistry has regularly been used for estimating proliferating cells fraction in the RMS to map physiological dynamics at various postnatal ages 15 and in several experimental interventions.…”
Section: Discussionmentioning
confidence: 87%
“…The proliferation activity of ependymal cells was assessed by the most commonly used markers of cell division: BrdU and Ki-67, respectively. BrdU immunohistochemistry has regularly been applied for estimating proliferating cells number in the main neurogenic region of the brain under physiological conditions [24] and in experimental interventions [25,26]. The more recently introduced marker, Ki-67 is also commonly used for detection of proliferation in the brain [27] and the spinal cord [16].…”
Section: Discussionmentioning
confidence: 99%